OPTIMALISASI PEMANFAATAN SUMBER DAYA UNTUK MENCIPTAKAN KEUNGGULAN BISNIS - Sukandi, Pipin; Hapsari, Ayuningtyas Yuli; Dalimunthe, Gallang Perdhana; Lisdayanti, Annisa; Nilasari, Irma (Jurnal Abdimas Bina Bangsa, 2024)
Optimizing resource utilization is a crucial strategy in creating business advantages in an era of increasingly fierce global competition. This community service activity examines how the company can maximize the use of its resources, both tangible and intangible, to improve operational efficiency and competitiveness in the market. The study combines analysis of the current literature with case studies from various industries to identify best practices in resource management. The main focus is given on four key aspects: human resources, technology, finance, and organizational knowledge. The results of this activity show that companies that successfully optimize their resources have several common characteristics, including: 1) the implementation of an integrated resource management system, 2) continuous investment in employee competency development, 3) the adoption of appropriate technology, 4) the strategic allocation of financial resources, and 5) an organizational culture that encourages continuous innovation and learning. Furthermore, this community service activity will be sustainable, including in business assistance.